GENE POLYMORPHISIM OF TRANSFORMING GROWTH FACTOR Beta 1(TGF-β1) IN AUTISM SPECTRUM DISORDER ASD IN BASRAH - Khulood, Abdulrazaq Kaleel; Wijdan, Nazar Ibraheim (Basrah Journal of Veterinary Research)
Transforming growth factor-β1 (TGF-β1) is an important immune regulatorcritical for immune homeostasis. Accumulating evidence suggests that TGF-β1 has acrucial regulatory role in CNS development and potential implications forneurogenesis in a variety of TGF-β1-related CNS diseases: so the aim of the study toinvestigate the association of the TGFβ-1 gene polymorphism with its plasma proteinplasma level (TGFB-1)in ASD patients, It's a case – control study atotal of 94 patientswith ASD, their age ranging from 2 to 13 years and 100 apparently healthy childrenwere used as a control which were matched by age and sex. TGFβ-1 levels wasmeasured by ELISA and TGF-β1(Codon 10 +869 C/T) and TGF-β1(Codon 25:+915*G/C)Gene Polymorphism were detected by specific sets of primers.The meanvalue of TGF-β1 was significantly low in the autistic group (95.91pg / mm) ascompare with the control one (117.08 pg / mm) TGF-β1(Codon 10: +869*T/C) genepolymorphism showed heterogeneous results between autistic group and controlgroup